Empowering Schools To Strengthen Students’ Religious Character Through Islamic Religious Education In The Society 5.0 Era - Ach Khusnan; Sutono (LPPM, STAI Al-Azhar Menganti, 2025)
Technological advancement in the Society 5.0 era has created both opportunities and challenges in education, particularly in the development of students' religious character. The extensive use of technology needs to be balanced with the strengthening of religious values so that students can utilize digital technology wisely and responsibly. This Community Service Program (PKM) aimed to empower schools in strengthening students' religious character through Islamic Religious Education (IRE) in the Society 5.0 era. The program was implemented at MI Tarbiyatul Muta’allimin Gresik and involved fifth- and sixth-grade students as the primary participants. A participatory approach was employed through several stages, namely observation, planning, program implementation, mentoring, and evaluation. The activities included mentoring Islamic Religious Education learning through interactive media, habituation of daily prayers and Asmaul Husna recitation, guidance in ablution and congregational prayer practices, Islamic etiquette education, and the utilization of Islamic educational videos as learning media. The results indicated an increase in students’ enthusiasm for participating in Islamic Religious Education learning, improved understanding of proper worship practices, the development of religious habits in daily life, and greater awareness of the positive use of digital technology. Furthermore, teachers and school administrators responded positively to the program as it contributed to the development of a more religious school culture. Therefore, school empowerment through Islamic Religious Education can serve as an effective strategy for strengthening students’ religious character while preparing them to face the challenges of the Society 5.0 era.